2002
DOI: 10.1007/bf02492478
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the performance of analytical methods based on solid-phase extraction and on solid-phase microextraction for the determination of antifouling booster biocides in natural waters

Abstract: SummaryAnalytical procedures based on solid-phase extraction (SPE) and solid-phase microextraction (SPME) have been compared for the determination of four organic booster biocides used in marine antifouhng paints (irgarol 1051, dichlofluanid, chlorothalonil, and sea-nine 211). Both techniques were coupled with gas chromatography with electron-capture, flame-thermionic, and mass-spectrometric detection. Recovery studies in spiked samples of water of different origin (distilled, lake, river, and sea water) demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…The slight differences in the data could be attributed to the retention of part of the biocides by the precipitated polymer when the adhesive polymer is precipitated with acetonitrile and by the more exhaustive extraction conditions of the three‐phase HF‐LPME method. The samples exhibited concentrations of isothiazolones in adhesives higher than those found in cosmetic products (soaps, creams) for direct use on the skin and body, whose values ranged from 1 to 15 μg/g, and well above the values found in water and wastewater sludge . The values found in this study are of the same order of magnitude as those reported in adhesives used in wallpaper with 4.4–10.4 μg/g for MIT and 13.7–26.5 μg/g for CMIT.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…The slight differences in the data could be attributed to the retention of part of the biocides by the precipitated polymer when the adhesive polymer is precipitated with acetonitrile and by the more exhaustive extraction conditions of the three‐phase HF‐LPME method. The samples exhibited concentrations of isothiazolones in adhesives higher than those found in cosmetic products (soaps, creams) for direct use on the skin and body, whose values ranged from 1 to 15 μg/g, and well above the values found in water and wastewater sludge . The values found in this study are of the same order of magnitude as those reported in adhesives used in wallpaper with 4.4–10.4 μg/g for MIT and 13.7–26.5 μg/g for CMIT.…”
Section: Resultssupporting
confidence: 59%
“…There are several analytical techniques available for sample preparation and the determination of isothiazolinone biocides in applications such as pharmaceuticals , adhesives , water , and wastewater . However, the most conventional techniques are tedious procedures that imply a high amount of solvent and provide high LODs.…”
Section: Introductionmentioning
confidence: 99%
“…Compare with LLE, SPE pretreatments has more peak number, and has bigger integral areas.Moreover, SPE method is solvent-free, sensitive and requires only very small amounts of samples for analysis [6][7]. SPE was a feasibleanalysis method for pretreatments for analysis of organic components in Landfill Leachat.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SDB and C18 (octadecyl) extraction disks were selected for the evaluation of extraction efficiency of the selected EDCs. SDB disks were selected as an alternative adsorbent to C18, containing binding sites with different mechanisms of adsorption, e. g., ion exchange, dispersion, hydrophobic interactions, and hydrogen bonding [38]. The results obtained are shown in Fig.…”
Section: Extraction Recovery With Different Extraction Disksmentioning
confidence: 99%